Motivasi Siswa dalam Pendidikan Islam di Era Digital: Sebuah Studi Kasus di Jawa Barat - Engkos Kosasih; Nia Oktaviani (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to describe the condition of student learning motivation, examine the utilization of digital technology, and identify various factors influencing learning motivation in Islamic Religious Education (PAI) for eighth-grade students at MTs Muhammadiyah Tanjungsari, Sumedang Regency,West Java, amidst the era of digital transformation. This research uses a qualitative approach with a case study design. Data was collected through in-depth interviews with eight students and two teachers, then analyzed using open coding, axial coding, and selective coding stages. The results show that student motivation in PAI learning is diverse. Some students have strong intrinsic motivation arising from religious awareness and the need to understand religious teachings. Others are influenced by external factors such as the role of teachers, parental support, and peer environment. On the other hand, amotivation was also found in some students. The use of digital technology can increase student engagement and interest in learning. However, its effectiveness is highly influenced by the availability of facilities and the teacher's ability to integrate technology appropriately into the learning process. Nevertheless, students still view direct explanations from teachers as the primary source for understanding material. Thus, technology functions as a support, not a replacement for pedagogical interaction. This study concludes that optimizing PAI learning motivation in the digital era requires alignment between students' internal drive, innovative learning strategies by teachers, social environmental support, and technological infrastructure readiness.